1981
DOI: 10.1111/j.1524-4725.1981.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Levels in Patients with Basal‐Cell Carcinoma

Abstract: Basal-cell carcinoma is a malignant epithelial neoplasm that arises from the germinative cells of the epidermis and its appendages. Various causative factors have been implicated in its pathogenesis. In recent years, it has become increasingly apparent that alterations in serum zinc concentration may relate to neoplastic diseases. The objective of this study was to determine whether or not a relationship exists between abnormal serum zinc levels and basal-cell carcinomas. The data indicate that a statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The present study dealing with the importance of zinc, SZC and to some extent SCC during malignancy and following successful treatment reveals that there was a change in the level of SZC with induction of tumor and it inversely correlated with the progression of a tumor. Depression of SZC has also been observed in several human malignancies [ 13 ]. In this study, SZC showed an inverse correlation with the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The present study dealing with the importance of zinc, SZC and to some extent SCC during malignancy and following successful treatment reveals that there was a change in the level of SZC with induction of tumor and it inversely correlated with the progression of a tumor. Depression of SZC has also been observed in several human malignancies [ 13 ]. In this study, SZC showed an inverse correlation with the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the changes which occur are often conflicting and may depend upon the zinc requirement of the particular tumor compared to normal tissue or whether the tissue in which the tumor develops has a relatively high zinc content (1). For example, a significant elevation of serum zinc was found in patients with basal-cell carcinoma (2), malignant tumor of the uterus (3), and primary osteosarcoma without metastases (4). Decreased zinc levels have been observed in the serum of patients with non-Hodgkin's lymphoma (5), lung cancer (6), and in the plasma of children with untreated leukemia (7).…”
mentioning
confidence: 98%